Ainu Representation in the World of Japanese Comics: Witnessing Indigenous Rights Violations in Japanese Graphic Life Narratives - Keller, Zsófia (Távol-keleti Tanulmányok, 2026)
Chiri Yukie and the Ainu (Chiri Yukie to Ainu 知里幸恵とアイヌ, 2018) and Song of the Kamuy (Kamuy no Uta カムイのうた, 2023) are both Japanese comics that fictionalize the life of Chiri Yukie (1903–1922), an Ainu poet whose first and only published work titled Collection of Ainu Chants of Spiritual Beings (Ainu Shinyōshū アイヌ神謡集, 1923) was one of the earliest efforts for the transmission of a living Ainu identity. This paper analyses the content of the above-mentioned manga by employing Olga Micheal’s methodology. In her book titled Human Rights in Graphic Life Narratives (2023), Michael theorizes that graphic life narratives—including Western comic books—have the potential to highlight or obscure the connection between the colonial history of the Global South and the current human rights violations committed against its inhabitants. Reformulating her theory to fit the Japanese context, this paper seeks to find out how the above-mentioned manga portray the interrelatedness of Hokkaidō’s status as a settler colony and the violation of the Ainu people’s indigenous rights during Yukie’s lifetime, when special primary schools were set up to mould Ainu children into dutiful Japanese citizens, and Ainu cemeteries were routinely robbed to satisfy the scientific curiosity of Wajin anthropologists. To different degrees, the above-mentioned manga both gloss over the role colonialism played in these injustices, just as they leave out that Yukie could be seen as a victim of the colonial power imbalance between her and Kindaichi Kyōsuke (1882–1971), the Wajin professor she worked with. Even though the ambiguity inherent in both stories’ portrayal of real-life events and sentiments is antithetical to the spirit of historical truthfulness, as advocated for by Tessa-Morris Suzuki (2005), they can be seen as something more than casual entertainment. In addition to transforming their readers into secondary witnesses, Chiri Yukie and the Ainu and Song of the Kamuy are both places of memory, as originally defined by Pierre Nora (2009). While the former is elevated to this status by virtue of being an educational gakushū manga, the latter is transformed by the activist stance taken by its creators against Ainu discrimination.